Pilgrims’ Cultural Contacts on Their Journey to the Hijaz from Bukhara in the 19th Century - Mustafa Tanrıverdi (Avrasya İncelemeleri Dergisi)
Although the pilgrimages of Turkestan Muslims to the Hijaz were interrupted from time to time, establishing cultural ties with the Ottoman Empire and Ottoman citizens was important to the pilgrims. Despite the presence of different routes for the long pilgrimage, reaching the Hijaz by way of Istanbul was a priority for Turkestani pilgrims. The Istanbul stop along the difficult and troublesome journey took on the function of both being a rest and way to strengthen cultural and religious ties. According to archival documents, the pilgrims from the Emirate of Bukhara made up a very significant number of the pilgrims from Turkestan who came to Ottoman lands. Great attention was paid to the Bukhara ulama and dervishes, and they were duly hosted in the places they visited. If they wished to stay for a long period of time, they were provided with the necessary facilities, with emphasis placed on their association with madrasahs and Sufi lodges. Toward the end of the 19th century, the pilgrimages intensified with the increase in transportation facilities; this was enough to worry Russia, which ruled Turkestan. The concern stemmed from the claim that pilgrimages played a role that could lead the Muslims of the region to separate from Russia in terms of religious and political independence. The aim of this study is to evaluate the cultural contacts the pilgrims from Bukhara had with Ottoman Muslims along the pilgrimage route based on Ottoman archival documents.